The prosecution of international crimes in respect of the Democratic Republic of the Congo: critical evaluation of the factual background and specific legal considerations - Materu, Sosteness F. (University of the Western Cape, 2013)
Magister Legum - LLM === The first part of this study evaluates the historical events that led to the referral of the DRC situation to the ICC. This includes the background of the conflict and the extent to which international crimes have been committed. Both regional and domestic attempts and initiatives to address the conflict are discussed, with specific reference to peace agreements and restorative justice mechanisms. The second part of the study deals with the prosecution of the perpetrators by the ICC. It examines the approach of the Pre- Trial Chamber to two legal issues, the principle of complementarity and modes of criminal participation as part of the ICC Statute. In this regard, the study makes a critical evaluation of two preliminary decisions confirming the charges against Lubanga, Katanga and Chui before the cases proceeded to the trial stage. === South Africa